Sistem Informasi Pengolahan Stok Sparepart Dengan Menggunakan Metode FIFO Pada Indocopier Berbasis Web - Tiovany Cristin Marbun; Niko Surya Atmaja; Surya Hendra Putra (Lembaga Pengembangan Kinerja Dosen, 2026)
This research aims to build a web-based sparepart stock processing information system at Indocopier to overcome manual recording issues that often lead to data inaccuracies and difficulties in monitoring stock circulation. The First-In, First-Out (FIFO) method is implemented into the system to ensure inventory management follows the entry sequence, thereby minimizing the risk of inventory stagnation or goods obsolescence. The system was developed using the PHP programming language with the [Insert Framework, e.g., Laravel/CodeIgniter] framework and MySQL database. The system development method used is Waterfall. The results of this study are an information system capable of managing incoming and outgoing goods data in real-time, providing accurate stock movement reports, and facilitating Indocopier management in making decisions regarding procurement. System testing using the Black Box Testing method demonstrates that all system functions operate in accordance with the expected functional requirements